Crystal structure of tris(1,8-diazabicyclo[5.4.0]undec-7-ene)[(μ12- phosphato)-tetracosakis(μ2-oxo)-dodecaoxo-dodeca-molybdenum], C27H51Mo12N6O40P - Xia Daocheng; Feng Feng (Zeitschrift für Kristallographie - New Crystal Structures, 2013)
C27H51Mo12N6O40P, trigonal, R3c (no. 161), a = 20.212(5) Å, c = 23.801(5) Å, V = 8420.8 Å3, Z = 6, Rgt(F) = 0.0318, wRref(F2) = 0.0610, T = 293 K.